The role of DAAO in cognitive impairment of offspring mice induced by arsenic exposure during early developmental stage - Zehua Niu; Xiao Xie; Xiaoxia Jin; Haiyang Yu; Ge Jin; Yan Wang (PLoS ONE, 2025)
Arsenic exposure model of offspring mice was established and intervened with 6-chlorobenzo[d]isoxazol-3-ol (CBIO), a D-amino acid oxidase (DAAO) inhibitor, to explore the role of DAAO in cognitive impairment of offspring mice induced by arsenic during early developmental stage. Female mice and their pups treated with 0 or 60 mg/L sodium arsenite (NaAsO2) via drinkable water from the first day of gestation till the end of lactation. On the 28th day after birth, the offspring mice in the drinking distilled water group were randomly divided into control and 1 mg/mL CBIO group. The offspring mice in the arsenic group were divided into 60 mg/L NaAsO2 group and 60 mg/L NaAsO2 + 1 mg/mL CBIO group, CBIO was administered to the lateral ventricle for one week. Additionally, D-serine and L-serine concentrations were detected by UHPLC-MS/MS, Real-time RT-PCR and Western blot were applied to measure DAAO, serine racemase (SR), N-methyl-D-aspartate receptor (NMDAR), synaptophysin (SYP) and postsynaptic density (PSD95) levels in the hippocampus. Results disclosed that arsenic could reduce the levels of D-serine, L-serine, SR and NMDAR, while upregulate DAAO levels, however, inhibiting DAAO levels could increase D-serine and NR1 levels. These findings indicated that DAAO might be involved in cognitive impairment of offspring mice induced by arsenic during early developmental stage by affecting D-serine metabolism.